COMMUNICATION STRATEGY IN PROVIDING INFORMATION ON TECHNICAL SERVICE FOR TESTING MOTORIZED VEHICLES AT CENTRAL ACEH TRANSPORTATION SERVICE - AB, Subhan; Harahap, Viana Safrida; Budi, Hasiun; Efendi, Muhsin; Basri, Hasan (Jurnal Ranah Komunikasi, 2024)
This study aims to investigate the communication strategies utilized by employees of the Transportation Service of Central Aceh in disseminating technical information about the Vehicle Roadworthiness Test (known as Uji KIR in Indonesia) to the public in Central Aceh Regency, while also identifying the obstacles that hinder their effectiveness in conveying the information. The employed data collection methods were interviews, literature studies, and observations. Furthermore, the obtained data were analyzed qualitatively. The research findings revealed that the communication strategy used by employees of the Transportation Service of Central Aceh in providing technical information on the Vehicle Roadworthiness Test was communication planning and management strategies. The Transportation Service of Central Aceh, particularly the head of the Workshop-and-Testing Division, undertakes a planning process that involves preparing and developing procedures for implementing the Vehicle Roadworthiness Test, evaluating the test directly in case of issues, and strategizing to disseminate information through the government’s internal media. To provide information about the Vehicle Roadworthiness Test, the Transportation Service of Central Aceh manages the implementation and preparation of a communication strategy that considers four factors: identifying the target audience, which includes owners of public transport vehicles; formulating messages to be conveyed to the vehicle owners; determining effective communication methods; and identifying the appropriate media for transmitting information to the vehicle owners. The purpose of communication planning and management strategies is to inform public transport vehicle owners about the procedure for taking the Vehicle Roadworthiness Test at the Transportation Service of Central Aceh.